New biomaterials for orthopedic implants - Ong KL; Yun BM; White JB (Orthopedic Research and Reviews, 2015)
Kevin L Ong, Brian Min Yun, Joshua B WhiteExponent, Inc., Philadelphia, PA, USAAbstract: With the increasing use of orthopedic implants worldwide, there continues to be great interest in the development of novel technologies to further improve the effective clinical performance of contemporary treatment modalities and devices. Continuing research interest also exists in developing novel bulk biomaterials (eg, polycarbonate urethanes, silicon) or novel formulations of existing but less widely used biomaterials (eg, polyaryletherketones, polyetheretherketone). There is also growing focus on customizing the material properties of bioabsorbables and composite materials with fillers such as bioactive ceramics. In terms of tissue engineering, more recent developments have focused on basic engineering and biological fundamentals to use cells, signaling factors, and the scaffold material itself to better restore tissue and organ structure and function. There has also been recent controversy with the use of injectables as a nonsurgical approach to treat joint disorders, but more attention is being directed toward the development of newer formulations with different molecular weights. The industry has also continuously sought to improve coatings to supplement the function of existing implants, with the goal of improving their osseointegrative qualities and incorporating antimicrobial properties. These include the use of bone morphogenetic protein, bisphosphonates, calcium phosphate, silicon nitride, and iodine. Due to the widespread use of bone graft materials, recent developments in synthetic graft materials have explored further development of bioactive glass, ceramic materials, and porous titanium particles. This review article provides an overview of ongoing efforts in the above research areas.Keywords: coatings, scaffolds, bioabsorbables, bone graft, injectables